2019
DOI: 10.1002/mds.27682
|View full text |Cite
|
Sign up to set email alerts
|

Mild cognitive impairment in de novo Parkinson's disease: A neuromelanin MRI study in locus coeruleus

Abstract: Background We aimed to investigate neuromelanin‐sensitive magnetic resonance imaging (NM‐MRI) features in the locus coeruleus of de novo Parkinson's disease patients with different cognitive states and to determine whether these features are associated with cognitive impairment. Methods Three groups of subjects were recruited in this study, including patients with de novo PD with mild cognitive impairment (n = 23), patients with de novo PD without cognitive impairment (n = 48), and control subjects (n = 32). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
57
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 53 publications
6
57
0
Order By: Relevance
“…The LC reveals degeneration and a loss of noradrenergic cells in alpha-synucleinopathies such as DLB (Iseki et al, 2001;Mori et al, 2002;Brunnström et al, 2011;Haglund et al, 2016, Table 1). The noradrenergic LC system often becomes degenerated early in both alpha-synucleinopathies such as Parkinson's disease (PD) (Solopchuk et al, 2018;Li et al, 2019), and ß-amyloidopathies like Alzheimer's disease (AD) (Zarow et al, 2003;Hou et al, 2021). Both diseases are closely related to Lewy body pathology, as mixed pathologies can coexist in patients with cognitive impairment (Coughlin et al, 2020).…”
Section: Degeneration Of the Locus Coeruleus In Dementia With Lewy Bomentioning
confidence: 99%
See 1 more Smart Citation
“…The LC reveals degeneration and a loss of noradrenergic cells in alpha-synucleinopathies such as DLB (Iseki et al, 2001;Mori et al, 2002;Brunnström et al, 2011;Haglund et al, 2016, Table 1). The noradrenergic LC system often becomes degenerated early in both alpha-synucleinopathies such as Parkinson's disease (PD) (Solopchuk et al, 2018;Li et al, 2019), and ß-amyloidopathies like Alzheimer's disease (AD) (Zarow et al, 2003;Hou et al, 2021). Both diseases are closely related to Lewy body pathology, as mixed pathologies can coexist in patients with cognitive impairment (Coughlin et al, 2020).…”
Section: Degeneration Of the Locus Coeruleus In Dementia With Lewy Bomentioning
confidence: 99%
“…The pathomechanism might be similar in both alphasynucleinopathies at an early stage in terms of the amount, type, and spread of Lewy bodies within the LC region. Via neuromelanin-sensitive MRI, a recent study (Li et al, 2019) showed that the LC's contrast-to-noise ratio in 23 PD patients with mild cognitive impairment was lower than in control subjects. They observed a negative relationship between reduced contrast to the LC and measures of executive dysfunction in these patients (Li et al, 2019) implying an early contribution by the LC-noradrenaline system to symptomatology in PD patients.…”
Section: Degeneration Of the Locus Coeruleus In Dementia With Lewy Bomentioning
confidence: 99%
“…Although dementia in PD is related to a substantial reduction in cortical cholinergic markers, there is also evidence for a more severe loss of noradrenergic input from the LC to cortical areas (Chan-Palay and Asan, 1989). The severity of dementia has been linked to the loss of LC neurons in some studies (Zweig et al, 1993;Del Tredici and Braak, 2013;Li et al, 2019).…”
Section: Cognitive Manifestationsmentioning
confidence: 99%
“…Such a strict correlation with LC-MRI features was not observed for cognitive and dysautonomic symptoms. In fact, in PD patients suffering from mild cognitive impairment (PD-MCI), LC intensity was reduced compared to HC, but there were no differences between cognitively unimpaired PD patients and PD-MCI ones [74,76]. Similar results were observed in parkinsonian subjects suffering from dysautonomic dysfunctions [74].…”
Section: Lc-mri In Healthy Subjectsmentioning
confidence: 53%
“…In PD, several authors have shown the occurrence of significant reduction of LC-MRI intensity [16,[69][70][71][72][73][74][75][76]. Noteworthy, and in line with post-mortem pathological observations [13], in PD patients, LC-MRI alteration is even more severe than the SN-MRI one [72,73].…”
Section: Lc-mri In Healthy Subjectsmentioning
confidence: 61%